2017
DOI: 10.3168/jds.2017-12689
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl-cellulose rumen-protected methionine enhances performance during the periparturient period and early lactation in Holstein dairy cows

Abstract: The onset of lactation in dairy cows is characterized by severe negative energy and protein balance. Increasing Met availability during this time may improve milk production, hepatic lipid metabolism, and immune function. The aim of this study was to evaluate the effect of feeding ethyl-cellulose rumen-protected methionine (RPM; Mepron, Evonik Nutrition and Care GmbH, Hanau-Wolfgang, Germany) on the performance of dairy cows during prepartum and early-lactation periods. Sixty multiparous Holstein cows were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
129
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(155 citation statements)
references
References 35 publications
16
129
5
2
Order By: Relevance
“…Our current results for DMI and milk production (Table ) were not consistent with previous findings: in other studies, DMI (Schingoethe et al., ; Sun et al., ), milk yield (Batistel et al., ), 4% fat‐corrected milk (Sun et al., ), or yield or percentage of milk protein (Patton, ) changed when RPMet was supplemented. According to AminoCow, using the data from the production trial (DMI, milk yield, milk content of protein and fat), only the adequacies of Lys and Met were less than 110%.…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…Our current results for DMI and milk production (Table ) were not consistent with previous findings: in other studies, DMI (Schingoethe et al., ; Sun et al., ), milk yield (Batistel et al., ), 4% fat‐corrected milk (Sun et al., ), or yield or percentage of milk protein (Patton, ) changed when RPMet was supplemented. According to AminoCow, using the data from the production trial (DMI, milk yield, milk content of protein and fat), only the adequacies of Lys and Met were less than 110%.…”
Section: Discussioncontrasting
confidence: 97%
“…In addition, Batistel et al. () reported that plasma γ‐glutamyl transpeptidase levels decreased when cows were supplemented with 15 g/day of RPMet. From these previous reports and our results, we infer that some plasma items might change when diets contain RPMet at 15 g/day or more, but supplementation at the rate we used did not affect plasma profiles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations